Studia teologiczne Franciszka Karola Blachnickiego w Uniwersytecie Jagiellońskim 1945-1950 oraz początki koncepcji świętości w jego teologii moralnej i pastoralnej - Tytko, Marek M. (Archiwa, Biblioteki i Muzea Kościelne, 2020)
The article concerns rev. Franciszek Karol Blachnicki (born 1920, died 1987). The paper shows early period of his life, it focus on theological studies, which took place at the Jagiellonian University in years 1945-1950. The author presents unknown (inedited) documents preserved in the Archives of the Jagiellonian University, archival records concerning his education according to the program of the theological studying in the Faculty of Theology and evaluation of his master’s work written by Blachnicki in 1950 year, concerning the essence of sainthood (holiness). The author of the article makes a hypothesis on theme relations between theological, ethical, pedagogical conceptions of Blachnicki’s masters and his own theological, ethical, pedagogical conceptions.